Evaluating fidelity of community health worker roles in malaria prevention and control programs in Livingstone District, Zambia-A bottleneck analysis - Helen Mwiinga Chipukuma; Hikabasa Halwiindi; Joseph Mumba Zulu; Steven Chifundo Azizi; Choolwe Jacobs (BMC, 2020)
Abstract Background Community Health Workers (CHWs) are an important human resource in improving community malaria intervention coverages and success in reducing malaria incidence has been attributed to them. However, despite this attribution, malaria resurgence cases have been reported in various countries including Zambia. This study aims to evaluate the implementation fidelity of CHW roles in malaria prevention and control programs in Livingstone through performance and service quality assessment. Methods A mixed method concurrent cross-sectional study based on quantitative and qualitative approaches was used to evaluate performance and service quality of the CHW roles for selected catchments areas in Livingstone district. For the quantitative approach, (34) CHWs were interviewed and a community survey was also done with 464 community participants. For qualitative approach, two focused group discussions with CHWs and three key informant interviews from the CHW supervisors were done. Results Overall implementation fidelity to the CHW roles was low with only 5(14.7%) of the CHWs having good performance and least good quality service while 29 (85.3%) performed poorly with substandard service. About 30% of house-holds reported having experienced malaria cases but CHWs had low coverage in testing with RDT (27%) for malaria index case service response with treatment at 14% coverage and provision of health education at 23%. For other households without malaria cases, only 27% had received malaria health education and 15% were screened for malaria. However, ITN distribution, sensitization for IRS were among other CHW services received by the community but were not documented in CHW registers for evaluation. Factors that shaped fidelity were being married, record for reports, supervision, and work experience as significant factors associated with performance. Lack of supplies, insufficient remuneration and lack of ownership by the supervising district were reported to hinder ideal implementation of the CHW strategy. Conclusion Fidelity to the malaria CHW roles was low as performance and quality of service was poor. A systems approach for malaria CHW facilitation considering supervision, stock supply and recruiting more CHWs on a more standardized level of recognition and remuneration would render an effective quality implementation of the CHW roles in malaria.